Active cytomegalovirus infection in mechanically ventilated patients with sepsis - Zhihui Zhang; Jierong Zhang; Shuang Dai; Xueying Fan; Yuhua Liu; Junlu Sun; Lisheng Chen; Tiantian Song; Shangzuo Li; Jinjiang Zhang; Xuesong Liu; Rong Zhang; et al. (BMC Infectious Diseases)
Abstract Background Active cytomegalovirus (CMV) infection is associated with poor prognosis in septic patients with critical illness. Patients of septic category are highly likely to benefit from prophylactic antiviral therapy. Nevertheless, the clinical characteristics for CMV reactivation are lacking among septic patients requiring mechanical ventilation. The aim of this study was to investigate the incidence, risk factors, and clinical outcomes regarding active CMV infection in mechanically ventilated patients with sepsis. Methods A single-center, retrospective cohort study conducted from January 2021 to December 2023 that included septic patients on mechanical ventilation at the intensive care unit (ICU) of a national hospital. Study participants were divided into active and non-active CMV infection groups based on CMV DNAemia within a 28-day hospitalization period in ICU. Clinical features, laboratory findings, treatment measures, and clinical outcomes were compared between the two groups. Results Among 118 septic patients, 21 (17.8%) exhibited active CMV infection within 28-day ICU admission. Hemoglobin served as an independent risk factor and predictor for active CMV infection (P < 0.05). Moreover, the duration of mechanical ventilation and ICU stay in active CMV infection patients were significantly higher than in the comparison group (P < 0.05). Conclusions Active CMV infection is common and associated with adverse clinical outcomes in mechanically ventilated patients with sepsis. A low level of hemoglobin is an independent risk factor for active CMV infection. Further prospective studies are warranted to assess the efficacy of initiating prophylactic and preemptive antiviral therapies among patients with sepsis disorders.